دراسة عددية حول رفع قدرة التحمل الحدية لأساس مستمر على تربة غضارية مسلحة بطبقة رقائق جيوتكنيكية مصنعة و وسادة رملية - حسن, مالك; عجيل, سميحة (Latakia University Journal -Engineering Sciences Series, 2017)
يهدف هذا البحث بشكل أساسي لدراسة الفائدة المثلى من استخدام الشرائح الجيوتكنيكية المصنعة (Geogrid) كتسليح لتحسين قدرة تحمل التربة وتخفيض الهبوط تحت الأساسات المستمرة المنفذة على تربة غضارية. لتحقيق هذا الهدف تم إجراء نمذجة عددية بطريقة FEM، لدراسة سلوك التربة المسلحة تحت الأساس، و لإجراء دراسة بارامترية لأهم العوامل المؤثرة على قدرة تحمل التربة و أهمها موقع طبقة الجيوغريد تحت الأساس. وقد أظهرت نتائج التحليل العددي أن إضافة طبقة تسليح إلى التربة يمكن أن يحسن من قدرة تحمل التربة بشكل واضح كما أنه يؤدي إلى تخفيض الهبوط الناتج تحت الأساس، وإن التشوه الحاصل في شرائح التسليح مرتبط بشكل مباشر بالهبوط، ووضع التسليح في التربة المسلحة يؤدي إلى توزيع للحمولات على مساحة أكبر ويؤدي إلى الإقلال من تركيز الإجهادات ويسبب توزع أفضل لهذه الإجهادات. وهذه الإعادة في توزيع الإجهادات تحت طبقات التسليح تؤدي إلى تخفيض الهبوط في الطبقات ذات قدرة التحمل الضعيفة التي تليها. This research study aims at investigating the potential benefits of using the reinforcement to improve the bearing capacity and reduce the settlement of strip footing on clay. To implement this objective, many numerical 2D-analyses by finite element method / Plaxis program were performed to study the behavior of reinforced soil foundation. And then we carry out a parametric study of the most effective parameter on bearing capacity. The results showed that the inclusion of reinforcement can significantly improve the soil’s bearing capacity and reduce the footing settlement. The strain developed along the reinforcement is directly related to the settlement. The results also showed that the inclusion of reinforcement can redistribute the applied load to a wider area, thus minimizing stress concentration and achieving a more uniform stress distribution. The redistribution of stresses below the reinforced zone can result in reducing the settlement of the underlying weak clayey soil.